Strategic communication with a small conflict of interest - Francesc Dilmé (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
This paper analyzes strategic information transmission between a sender and a receiver with similar objectives. We provide a first-order approximation of the equilibrium behavior in the general version of the Crawford and Sobel's (1982) model with a small bias. Our analysis goes beyond the usual uniform-quadratic setting: we uncover how the state-dependent bias and the non-uniform state distribution influence the precision with which each state of the world is communicated. We illustrate the approach by providing novel comparative statics results in different applications.
Keywords: C72; D82; D83; 330; Strategic Communication; Small Bias